Cuffless Blood Pressure Measurement Using a Microwave Near-Field Self-Injection-Locked Wrist Pulse Sensor - Tseng, Chao-Hsiung; Tseng, Tzu-Jung; Wu, Cheng-Zhou (IEEE transactions on microwave theory and techniques, 2020)
A new cuffless methodology of measuring the blood pressures (BPs) of human subjects is designed using a microwave near-field self-injection-locked (NFSIL) wrist pulse sensor. The NFSIL wrist pulse sensor is primarily composed of a self-oscillating complementary split-ring resonator and an amplitude-based demodulator. It generates a concentrated electric field in the near-field region for wrist pulse waveform detection. The reflective pulse transit time is extracted from this measured wrist pulse waveform and substituted into the BP computation algorithm to estimate the systolic and diastolic BPs (DBPs) of the subjects being tested. In this article, four calibration factors are adopted in the BP computation formulas to improve the accuracy of the calculated systolic BPs. In addition, the calibration procedures of the proposed NFSIL BP sensor are clearly summarized and experimentally verified. The BPs of a young healthy subject are measured using the NFSIL BP sensor at five designated times for eight days continuously. Compared with the BP measured by the commercial sphygmomanometer, the mean difference and standard deviation of the systolic and DBPs of the subject are 0.26 ± 3.67 and 0.56 ± 6.99 mmHg, respectively. In addition, to verify the generalizability, ten test subjects aged from 23 to 48 years are recruited to measure BPs for five days continuously. The measured results in this study demonstrate the effectiveness of BP measurement using the proposed NFSIL BP sensor. Due to the advantages of having a simple system architecture, compact sensor size, low cost, and high sensitivity, the proposed NFSIL BP sensor has great potential for development as a commercial cuffless BP sensor for overnight BP monitoring.